Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/dmcn.12246
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions for children with cerebral palsy: state of the evidence

Abstract: Aim The aim of this study was to describe systematically the best available intervention evidence for children with cerebral palsy (CP). Method This study was a systematic review of systematic reviews. The following databases were searched: CINAHL, Cochrane Library, DARE, EMBASE, Google Scholar MEDLINE, OTSeeker, PEDro, PsycBITE, PsycINFO, and speechBITE. Two independent reviewers determined whether studies met the inclusion criteria. These were that (1) the study was a systematic review or the next best avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
1,060
3
40

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,095 publications
(1,187 citation statements)
references
References 220 publications
29
1,060
3
40
Order By: Relevance
“…Of the interventions identified in this study, a systematic review of interventions for CP found strong evidence that casting improved passive range of motion of the lower limb, botulinum toxin injections reduced lower-limb spasticity, and aerobic exercise improved aerobic fitness (Novak et al, 2013). This study found that 76% of therapists reported using serial casting, 81% reported using botulinum toxin, and 76% reported using cardiovascular exercise with gym equipment at least once in the past year.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Of the interventions identified in this study, a systematic review of interventions for CP found strong evidence that casting improved passive range of motion of the lower limb, botulinum toxin injections reduced lower-limb spasticity, and aerobic exercise improved aerobic fitness (Novak et al, 2013). This study found that 76% of therapists reported using serial casting, 81% reported using botulinum toxin, and 76% reported using cardiovascular exercise with gym equipment at least once in the past year.…”
Section: Discussionmentioning
confidence: 71%
“…This study found that 76% of therapists reported using serial casting, 81% reported using botulinum toxin, and 76% reported using cardiovascular exercise with gym equipment at least once in the past year. Although these interventions were recommended by Novak et al (2013) to be included in standard care for children with CP, there was insufficient evidence to support the use of casting or aerobic exercise to improve gross motor function and only moderate quality evidence to support the use of botulinum toxin in combination with physiotherapy for improving walking function among children with CP (Novak et al, 2013). Novak et al (2013), also recommended that neurodevelopmental therapy be discontinued from CP care as there was low quality evidence that it did not improve normalized movement, prevent contracture development, improve function, or enhance social emotional and cognitive skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, there has been a rapid increase in evidence from clinical trials for a variety of upper limb therapies for children with unilateral cerebral palsy (Novak, McIntyre, Morgan, Campbell, Dark, Morton et al, 2013;. Despite there being over 45 published randomized trials, there is a lag in the uptake of this evidence into clinical practice.…”
Section: Introductionmentioning
confidence: 99%